Penerapan analisis COSO pada perusahaan dagang - Nabilah, Sakinah Ilfi; Nursaputri, Dinda Dwi (Maliki Interdisciplinary Journal, 2024)
A trading company is a type of business that initially becomes a supplier and then sells it to consumers who need it. Qualitative research methods that aim to be able to understand the aspects and activities of the research subjects. Qualitative has data properties that can be developed in a narrative, presentation description or the frequency of the data. The purpose of this study is to understand the application of COSO-based internal control in trading companies. It can be concluded from this research that the concept of COSO in 2023 is the internal control of a company, but there is still no consistency in the procedures for its implementation.